The Value of Legal Education in The Resolution of Marital Property Disputes by The Religious Court of Kediri City Perspective Compilation of Islamic Law (KHI)) - Nurbaedah, Nurbaedah (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
The purpose of this article is to provide legal education to the public on the resolution of joint property disputes from the perspective of the Compilation of Islamic Law (KHI). Specifically, the author casuistically examined the decisions of the Kediri City Religious Court regarding the resolution of marital property disputes. This article was compiled using qualitative methods with this type of case study. The article concludes that the Kediri City Religious Court's decisions are quite flexible and contextual. This is reflected in several cases where, on one occasion, the Kediri City Religious Court had given a ruling on the settlement of property disputes related to Article 97 of the KHI while considering Article 89 paragraph 1 of Law No. 7 of the Year 1989 on Religious Justice. Then, on another occasion, the Kediri City Religious Court also excluded Article 97 of the KHI as a consideration in ruling on the settlement of marital property disputes because it was considered unfair based on the facts before the trial. This means that judges have the authority to position the principle of justice and contextual expediency as key in the resolution of community property disputes, which goes far beyond the normative side or formal legal aspects of the law.